2011
DOI: 10.1002/nme.3182
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional hybrid meshfree‐Cartesian scheme for fluid–body interaction

Abstract: SUMMARYA numerical method based on a hybrid meshfree-Cartesian grid is developed for solving three-dimensional fluid-solid interaction (FSI) problems involving solid bodies undergoing large motion. The body is discretized and enveloped by a cloud of meshfree nodes. The motion of the body is tracked by convecting the meshfree nodes against a background of Cartesian grid points. Spatial discretization of secondorder accuracy is accomplished by the combination of a generalized finite difference (GFD) method and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…Some experiments are performed for investigating the eect of such an initial angle showing that the nal descent mode is not aected as long as the initial angle is not "too large". A similar behavior has been observed in experimental studies of falling thin disks [3,33], thick disks [34] and also in numerical simulations on a falling torus released with an initial angle of 30 • [21]. Eect of an initial angle is illustrated in Fig.…”
Section: Descent Modessupporting
confidence: 84%
See 1 more Smart Citation
“…Some experiments are performed for investigating the eect of such an initial angle showing that the nal descent mode is not aected as long as the initial angle is not "too large". A similar behavior has been observed in experimental studies of falling thin disks [3,33], thick disks [34] and also in numerical simulations on a falling torus released with an initial angle of 30 • [21]. Eect of an initial angle is illustrated in Fig.…”
Section: Descent Modessupporting
confidence: 84%
“…For this low Re range, never reached during the present study, the rings underwent a steady vertical translation. The same motion is reported in the numerical work of Yu et al [21] for a torus of aspect ratio of 2 falling at Re = 25 or 50, and a detached axisymmetric recirculation bubble forms in the wake. This study also showed that when the torus is released with an angle of 30 • it returns to the horizontal (0 • ) after a few damped oscillations.…”
Section: Introductionsupporting
confidence: 84%
“…The standard seven-point central finite difference scheme is applied at Cartesian grid nodes that do not have mesh-free nodes nearby, while the singular value decomposition-generalized finite difference (SVD-GFD) scheme is applied at the mesh-free nodes and Cartesian nodes with mesh-free nodes nearby. Solutions by this scheme have been discussed in detail by Chew, Yeo & Shu (2006), Wang et al (2008Wang et al ( , 2010, Yu et al (2011) and Zhang (2013). The configuration of the nodal mesh around the model hawkmoth is shown in figure 31(a).…”
Section: Concluding Summarymentioning
confidence: 99%
“…The system may become under-determined when the small singular values were omitted, but the SVD method ensures a solution with minimum L 2 error can be obtained. The SVD scheme with regularization has been found to be robust and accurate in the practice of 3D simulations for natural flyers and swimmers [11,17,18]. …”
Section: Svd-gfd Schemementioning
confidence: 99%